Thallium Intoxication in Relation to Drug Abuse and Cigarette Smoking in Iran - Banafshe, Hamid Reza; Ghaderi, Amir (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Thallium (Tl) is a highly toxic heavy metal with atomic number 81. It is a soft, bluish-white or gray water-insoluble metal but the salt forms are colorless, tasteless, and odorless. Tl is readily absorbed via ingestion, inhalation, and dermal contact. Any amount of Tl in the body is abnormal. The clinical manifestation of thallotoxicosis has a wide spectrum but painful ascending peripheral neuropathy, gastrointestinal, and dermatologic manifestations are major characteristics in Tl toxicity. Tl intoxication has been identified in drug abuse and cigarette smoking leading to various signs and symptoms. Substance abuse and cigarette smoke are a major public health hazard across the world.